INCREASING THE LEVEL OF FINANCIAL LITERACY OF STUDENT YOUTH - Бугель, Юлія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
Today, the issue of raising the level of financial literacy of student youth in Ukraine is recognized as one of the most important, which is considered by the world economic community. The scientific elaboration of this issue becomes especially relevant in the context of finding ways to modernize and reform it. The purpose of the study is to suggest ways to increase the level of financial literacy of student youth. To achieve this goal, the article uses general and special research methods, in particular: general scientific and special research methods – to ensure the achievement of this goal; abstract-logical and dialectical methods of analysis – to substantiate theoretical positions and conclusions. The relevance of the material presented in the scientific article is due to the need to increase the level of financial literacy of young students. The main stages of realization of the national program of increase of financial literacy of students youth are investigated. Ways to increase the level of financial literacy of student youth in Ukraine are proposed. It is concluded that the proposed measures will contribute to the effective development of the state economy, social stability and improve the living standards of citizens.The relevance of the material presented in the scientific article is due to the need to increase the level of financial literacy of young students. The main stages of realization of the national program of increase of financial literacy of student's youth are investigated. Ways to increase the level of financial literacy of student youth in Ukraine are proposed. It is concluded that the proposed measures will contribute to the effective development of the state economy, social stability and improve the living standards of citizens. It is emphasized that the low level of financial literacy of student youth leads to ineffective decisions, increased own debt, improper savings, etc. Insufficient level of knowledge of young students in the field of financial services from a macroeconomic point of view means too low level of involvement of young students in their consumption. Students need to understand that a competent person in the field of finance is extremely necessary today. The obtained results of the research in the form of proposals and recommendations can be used by our state during the formation of strategic vectors of development of the educational space of Ukraine in the global environment.